DIGITAL CALIPER VS. INTRAORAL SCANNER: ACCURACY OF UPPER INTER-CANINE WIDTH MEASUREMENTS IN STUDY MODELS - Williem, Rachel Victoria; Tanjung, Rizki; Siti Salsabila Kirana; Anggraini, Wita; Lubis, M. Novo Perwira; Farizka, Intan (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
The upper canine teeth exhibit significant sexual dimorphism, making them frequently used in gender identification in forensic odontology. The measurement of the inter-canine width can be performed using conventional methods, such as a digital caliper, or modern methods using an intraoral scanner. The intraoral scanner offers higher accuracy and easier data storage; however, no studies have compared the inter-canine width of the upper jaw using both methods. This study measured the inter-canine width of the upper jaw on 80 jaw models using both instruments, with each measurement performed three times per instrument. The measurement results were analyzed using SPSS, with Intraclass Correlation Coefficient (ICC) for agreement, Kolmogorov-Smirnov for normality, and Independent T-test for significance. The ICC results showed good agreement (0.892), and the Independent T-test revealed no significant difference (p = 0.598). It can be concluded that there is no significant difference between the measurement of the upper inter-canine width using the intraoral scanner and the digital caliper.